Immune escape mechanisms of severe fever with thrombocytopenia syndrome virus - Wang, Tong; Xu, Ling; Zhu, Bin; Wang, Junzhong; Zheng, Xin (Frontiers in Immunology, 2022)
Severe fever with thrombocytopenia syndrome (SFTS), which is caused by SFTS virus (SFTSV), poses a serious threat to global public health, with high fatalities and an increasing prevalence. As effective therapies and prevention strategies are limited, there is an urgent need to elucidate the pathogenesis of SFTS. SFTSV has evolved several mechanisms to escape from host immunity. In this review, we summarize the mechanisms through which SFTSV escapes host immune responses, including the inhibition of innate immunity and evasion of adaptive immunity. Understanding the pathogenesis of SFTS will aid in the development of new strategies for the treatment of this disease.